Cross-Cultural Evidence for Apparent Racial Outgroup Advantage: Congruence between Perceived Facial Aggressiveness and Fighting Success - Třebický, Vít; Saribay, S Adil; Kleisner, Karel; Akoko, Robert Mbe; Kočnar, Tomáš; Valentova, Jaroslava Varella; Varella, Marco Antonio Correa; Havlíček, Jan (Scientific reports, 2018)
Research into face processing consistently shows an outgroup disadvantage in areas such as recognition memory and emotional identification. Potential ingroup advantage with respect to inferences regarding personality and behavioural outcomes, on the other hand, has not yet been studied. In the present study, we used the faces of male professional mixed martial arts (MMA) fighters of apparent African, European, or mixed-race origin as targets and males from four distant populations that vary in ethnic composition as perceivers. We compared the perceivers' inferences about targets' aggressiveness with the fighters' actual performance in professional MMA championships. Surprisingly, across three distant populations used in the study (Cameroon, Czech Republic, and Turkey), perceivers' inferences based on face rating were more congruent with real-world performance for targets belonging to an apparent racial outgroup (as opposed to ingroup). In an ethnically mixed population (Brazil), perceivers showed the lowest congruence for apparently mixed-race targets. It thus seems that the outgroup disadvantage observed in other face processing domains does not carry over to inferences about aggressive behavioural outcomes. In fact, it seems that this relationship is, if anything, reversed.
Keywords: dospělí; Emotions; Female; srovnání kultur; Adult; mladý dospělý; ženské pohlaví; Adolescent; emoce; interpersonální vztahy; lidé; rozpoznávání obrazu; agrese; Male; Social Perception; Young Adult; Cross-Cultural Comparison; Pattern Recognition, Visual; Aggression; lidé středního věku; Interpersonal Relations; mužské pohlaví; sociální percepce; Middle Aged; mladiství; Humans